The Treasury in public policy-making - Chapman, Richard A. (Studies in public policy-making., 1997)
Analyses the Treasury's role in public policy making and makes an original contribution to knowledge about the current work of the Treasury. The book focuses on three main areas:* the development of the Treasury from earliest times to the present* the current structure and organization of the Treasury following the radical changes which took place in 1995 as a result of the 1994 Fundamental Expenditure Review* the Treasury's role in the financing and responsibility of Next Step Agencies, including brief case studies of the Civil Service College, the Contributions Agency and the.